Improving High Order Thinking Skills (HOTS) Through the Trikaya Parisudha Learning Model - Astawan, I Gede; Dyan Anggreni, Ni Made; Eko Atmojo, Setyo; Ardiansyah, A. (International Journal of Elementary Education, 2021)
Problems in education have always been an essential issue in every country, including Indonesia. Almost all Indonesian students only master the lessons up to level 3 only. Meanwhile, many students from developed and developing countries have mastered lessons up to 4, 5, and even 6. The purpose of this study is to analyze the differences in High Order Thinking Skills (HOTS) between the groups given the Trikaya Parisudha Learning Model (MPTP) and those given the Conventional Learning Model. (MPK). This research is a quasi-experimental with pretest-posttest control group design. The research population is PGSD students in 7 classes. From the 7 classes, 4 classes were selected using random cluster sampling two classes as the experimental group and the other two classes as the control group. MPTP taught the experimental group. Meanwhile, the control group was taught with MPK. The methods used to collect data are observation, interviews, and questionnaires. The instrument used to collect data is the observation sheet. The data analysis technique used is descriptive statistics and inferential statistics. The results showed differences in student HOTS between the group given MPTP and the group given MPK. There is a difference in Critical Thinking Skills between the group given MPTP and the group given MPK. There are differences in Creative Thinking Skills between the group receiving MPTP and the group receiving MPK. It can be concluded that the Trikaya Parisudha Learning Model can improve students' higher order thinking.